Striped Sod Webworm (Larva), Changeable Grass-Veneer (Adult) Fissicrambus mutabilis (Clemens) (Insecta: Lepidoptera: Crambidae) - Anthony Coffey; Eileen Buss (EDIS, 2025)
The Featured Creatures collection provides in-depth profiles of insects, nematodes, arachnids and other organisms relevant to Florida. These profiles are intended for the use of interested laypersons with some knowledge of biology as well as academic audiences. This publication describes the striped sod webworm, a turfgrass pest that also damages wheat and corn. The publication describes the pest's morphology, natural history and range in the United States; lists potential host plants and damage the pest can cause; and provides advice on management strategies.